2014
DOI: 10.1590/s1415-43662014000600013
|View full text |Cite
|
Sign up to set email alerts
|

Forças verticais e de atrito em silos cilíndricos com fundo plano

Abstract: A predição exata das forças que atuam no corpo de um silo é um dos principais problemas, no que tange ao quesito dimensionamento dessas estruturas. Com o objetivo de mensurar as forças atuantes no fundo e nas paredes dos silos durante o processo de descarregamento foram instrumentados, por meio de células de carga e células de pressão, a parede e o fundo de um silo piloto vertical cilíndrico com fundo plano. As leituras das células foram realizadas por sistema automático de aquisição de dados durante o carrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…Amorphous solids promoting larger points of contact between particles and walls, consequently compromising the powders' flow. According to Lopes Neto et al (2014), the greater the roughness of the surface of the particle and/or the wall, the larger the frictional force absorbed by it. For spray drying samples with 15% maltodextrin, the opposite effect was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Amorphous solids promoting larger points of contact between particles and walls, consequently compromising the powders' flow. According to Lopes Neto et al (2014), the greater the roughness of the surface of the particle and/or the wall, the larger the frictional force absorbed by it. For spray drying samples with 15% maltodextrin, the opposite effect was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Lopes Neto et al (2014a) carried out a theoreticalexperimental analysis in a model silo with dry sand stored as a product, noting that the values of vertical pressures for the concentric unloading of the AS 3774 and ISO 11697 (1995) standards were the most adequate but 15% higher than the experimental values. When analyzing the efforts in a cylindrical silo with H/D ratio equal to 2, Couto et al (2013) observed that the values calculated by the recommendations of EN 1991-4 standard also overestimated the experimental results.…”
Section: Resultsmentioning
confidence: 99%
“…The large number of variables involved hampers a mathematical formalism capable of adequately expressing the phenomenon and that is applied with an acceptable margin of safety and economy (Calil Júnior et al, 2009). Many studies have been developed for the determination of pressures in silos using Janssen's theory (Lopes Neto, 2009;Nascimento & Calil Junior 2009;Ramírez et al, 2010;Ding et al, 2011;Silva et al, 2011;Lopes Neto et al, 2014a), however, in Brazil, the calculation procedures are not standardized.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have been conducted with reference to the determination of pressures acting on flat bottom silos (Diniz & Nascimento, 2006;Balevičius et al, 2011;Gallego et al, 2011;Rotter & Sadowski, 2012;Nascimento et al, 2013;Lopes Neto et al, 2014;Wen et al, 2015;Horabik et al, 2016;Wang et al, 2016;Pieraccini et al, 2017;Frank et al, 2018). However, there is a need for studies on the use of new materials for the flat bottom of these silos, which are elements subject to dynamic, often non-uniform loads.…”
Section: Introductionmentioning
confidence: 99%